Parametric and adsorption kinetic studies of reactive black 5 removal from textile simulated sample using oil palm (Elais Guineensis) empty fruit bunch - Quek, Kye Shane (2014)
The potential of empty fruit bunch as a low-cost biosorbent for the removal of Reactive Black 5 from aqueous solution was investigated in this study. The influences of pH, contact time, initial concentration and biosorbent dosage were studied in batch experiments at room temperature. The empty fruit bunch used in this study was characterized by mR spectroscopy and it was found that O-H, N-H, and C=O stretching were present. Maximum adsorption uptake of Reactive Black 5 dye was found to be at pH 2. At pH 2, the adsorption was rapid at the first 5 minutes of contact, with uptake of more than 50%, and equilibrium was achieved in 30 minutes of agitation. It was also found that higher biosorbent dosage increases dye uptake, of up to 90%. Kinetic studies showed good correlation coefficient for a pseudo-second-order kinetic model. Langmuir, Freundlich, and BET isotherm models were applied to describe the biosorption of Reactive Black 5 dyes onto empty fruit bunch. Langmuir model fitted the equilibrium data better, giving correlation coefficient of 0.9999 and a maximum adsorption capacity of 7.3421 mg/g. Both pseudo-second-order kinetic model and Langmuir model indicates monolayer coverage on adsorbent. The results showed that empty fruit bunch have the potential to be applied as alternative low-cost biosorbent in the remediation of dye contamination in waste water.